Answer:
x = 1 ±2sqrt(5)
Step-by-step explanation:
2x^2-4x-9=29
Add 9 to each each side
2x^2-4x-9+9=29+9
2x^2-4x=38
Divide by 2
2/2x^2-4/2x=38/8
x^2 -2x =19
Complete the square
x^2 -2x + (-2/2)^2 = 19 +(-2/2)^2
x^2 -2x +1 = 19+1
(x-1)^1=2 = 20
Take the square root of each side
sqrt((x-1)^2) = ±sqrt(20)
x-1 = ±sqrt(20)
Add 1 to each side
x-1+1 = 1 ±sqrt(20)
x = 1 ±sqrt(20)
Simplifying the square root of 20
x = 1 ±sqrt(4)sqrt(5)
x = 1 ±2sqrt(5)
A because the graph of a direct proportion crosses the origin.
Don't forget to vote brainliest and follow me!!!
Answer:
<h2>(2x - 3y)(4x - y) = 8x² - 14xy + 3y²</h2>
Step-by-step explanation:
Use FOIL: <em>(a + b)(c + d) = ac + ad + bc + bd</em>
(2x - 3y)(4x - y) = (2x)(4x) + (2x)(-y) + (-3y)(4x) + (-3y)(-y)
= 8x² - 2xy - 12xy + 3y²
<em>combine like terms</em>
= 8x² + (-2xy - 12xy) + 3y² = 8x² - 14xy + 3y²
9514 1404 393
Answer:
a. (-1/2, 5)
Step-by-step explanation:
The coefficients of x have opposite signs, so the x-terms can be eliminated by adding the two equations.
(2y -12x) +(3y +12x) = (16) +(9)
5y = 25 . . . . . . simplify
y = 5 . . . . . . . . .divide by 5
This matches only answer choice A.
__
<em>Check</em>
The other part of answer choice A is x = -1/2. We can test this to make sure it works:
2(5) -12(-1/2) = 16
10 + 6 = 16 . . . . . . true, the selected answer works OK